Strategi Menciptakan Entrepreneur Andal Melalui Pendidikan Teori 4P Untuk Pengembangan Kreativiatas Dalam Pendidikan Entrepreneurship - Sabtarini Kusumaningsih; Titik Rianawati (Jurnal Publikasi Ilmu Manajemen, 2023)
The purpose of this study is to find out the strategies used in developing creativity in entrepreneurship education through 4P theory education in order to create reliable entrepenuers. The method used in this study is a qualitative descriptive method by utilizing qualitative information or data which is described descriptively with the intention of exploring a phenomenon or social reality. The variables used in this research are strategy, creativity development, entrepreneur, 4P theory education, dan entrepreneurship education. The result of this study are by using learning strategies through 4P theory education and developing creativity, reliable entrepreneure can be created.